Five new species of Pachygenium (Schltr.) Szlach., R. González & Rutk. (Spirantheae, Cyclopogoninae, Orchidaceae) from Brazil - Mytnik-Ejsmont, Joanna; Rutkowski, Piotr; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2008)
Five new species of Pachygenium (Schltr.) Szlach., R. González & Rutk. (Spirantheae, Cyclopogoninae, Orchidaceae) from Brazil are described and illustrated. Their taxonomic position is briefly discussed. The genus is compared with Pelexia Poit. ex Rich., and the taxonomic status of both genera is discussed.